2020
DOI: 10.3389/fcell.2020.573487
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane (Saccharum officinarum L.) Top Extract Ameliorates Cognitive Decline in Senescence Model SAMP8 Mice: Modulation of Neural Development and Energy Metabolism

Abstract: Age-related biological alterations in brain function increase the risk of mild cognitive impairment and dementia, a global problem exacerbated by aging populations in developed nations. Limited pharmacological therapies have resulted in attention turning to the promising role of medicinal plants and dietary supplements in the treatment and prevention of dementia. Sugarcane ( Saccharum officinarum L.) top, largely considered as a by-product because of its low sugar content, in fact contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 100 publications
0
21
0
Order By: Relevance
“…CQA provided at 5 mg/kg for 30 days was reported to enhance brain function of SAMP8 mice as demonstrated in the Morris water maze test [ 64 ]. Consistently, microarray analysis showed that sugarcane top ethanolic extract regulated neuron development-associated genes in the cerebral cortex of SAMP8 mice [ 63 ]. Isoorientin is a naturally occurring C -glycosyl flavone and exists in several dietary plants, including corn silks [ 65 ], rooibos tea [ 66 ], and buckwheat [ 67 ].…”
Section: Anti-aging Effects Of Polyphenolsmentioning
confidence: 89%
See 1 more Smart Citation
“…CQA provided at 5 mg/kg for 30 days was reported to enhance brain function of SAMP8 mice as demonstrated in the Morris water maze test [ 64 ]. Consistently, microarray analysis showed that sugarcane top ethanolic extract regulated neuron development-associated genes in the cerebral cortex of SAMP8 mice [ 63 ]. Isoorientin is a naturally occurring C -glycosyl flavone and exists in several dietary plants, including corn silks [ 65 ], rooibos tea [ 66 ], and buckwheat [ 67 ].…”
Section: Anti-aging Effects Of Polyphenolsmentioning
confidence: 89%
“…Supplementation of EC (10 mg/kg) per day for two weeks significantly ameliorated 6-hydroxydopamine (OHDA)-lesioned PD behavior, including increased locomotor activity and decreased rotational behavior, as compared with sham operated control group in male rats, suggesting a neuroprotective property of this compound [ 62 ]. Sugarcane ( Saccharum officinarum L.) top ethanolic extract was reported to contain several polyphenols with strong antioxidant effects, including 3-caffeoylquinic acid (CQA), 5-CQA, 3-O-feruloylquinic acid (FQA), and isoorientin [ 63 ]. CQA provided at 5 mg/kg for 30 days was reported to enhance brain function of SAMP8 mice as demonstrated in the Morris water maze test [ 64 ].…”
Section: Anti-aging Effects Of Polyphenolsmentioning
confidence: 99%
“…Therefore, identifying the bioactive compounds of interest in a plant extract and understanding their targeted pathways responsible for the observed health benefits need to be well understood to exploit their full potential [ 38 ]. In our previous study, we reported that STEE exerts beneficial effects on aging-related cognitive health by promoting neuronal differentiation and neuronal energy metabolism and extending the length of the astrocytic process in vitro [ 19 ]. We have identified four major polyphenols rich in STEE.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported that oral administration of sugarcane top (ST) ethanolic extract (STEE) could ameliorate spatial learning and memory deficits in senescence-accelerated prone mouse 8 (SAMP8) that progressively develop aging phenotype. STEE improved cortical neurotransmission and stimulated hippocampal neurogenesis [ 19 ]. In vivo omics analysis and in vitro experiments with cultured cells have suggested the activation of pathways related to energy metabolism and neurodevelopment is the main mechanism underlying the above effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation